2016
DOI: 10.1177/1087057116652065
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Kinetic Binding Properties of Unlabeled Ligands via a Preincubation Endpoint Binding Approach

Abstract: The dissociation rates of unlabeled drugs have been well studied by kinetic binding analyses. Since kinetic assays are laborious, we developed a simple method to determine the kinetic binding parameters of unlabeled competitors by a preincubation endpoint assay. The probe binding after preincubation of a competitor can be described by a single equation as a function of time. Simulations using the equation revealed the degree of IC50 change induced by preincubation of a competitor depended on the dissociation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, AS-MS technolo-gy can be used to classify compound binding sites 1) and determine the dissociation rate constant of compounds. 16) Recently, in addition to classical small molecule approaches, various therapeutic modalities such as antibodies, peptides, and gene and cell therapies have come under development, and small drug molecules are being investigated for target protein degradation and small molecule drug targeting of RNA chains. In this environment, the value of small molecule drug discovery will refine and likely increase, and AS-MS technology can contribute to these efforts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AS-MS technolo-gy can be used to classify compound binding sites 1) and determine the dissociation rate constant of compounds. 16) Recently, in addition to classical small molecule approaches, various therapeutic modalities such as antibodies, peptides, and gene and cell therapies have come under development, and small drug molecules are being investigated for target protein degradation and small molecule drug targeting of RNA chains. In this environment, the value of small molecule drug discovery will refine and likely increase, and AS-MS technology can contribute to these efforts.…”
Section: Resultsmentioning
confidence: 99%
“…A study of target prioritization has been reported using the nuclear factor-kappaB (NF-κB) pathway. 15) This enables strategic allocation…”
Section: Current Topicsmentioning
confidence: 99%
“…Experimentalists are encouraged to use the MC simulations presented here for detailed evaluation of their own procedures (adjustments may be necessary if they differ significantly from the kPCA assay set‐up, Schiele et al, ) and to address the remaining open questions, such as the influence of ligand and target depletion. Along these lines, further studies could include the expansion of these analyses to recent variants of the “kinetics of competitive binding” equation that incorporate alternative scheduling of the labelled and unlabelled ligand addition (Hoare, ; Shimizu, Ogawa, & Nakayama, ) or two‐state binding (Guo et al, ). All in all, this work should enable the optimised design and analysis of competition association assays.…”
Section: Discussionmentioning
confidence: 99%
“…AS-MS technology is a simple, accurate, and universal label-free binding assay technology that can be applied in high-throughput drug discovery and protein target identification 128 . Furthermore, AS-MS technology can be used to classify compound binding sites and determine the dissociation rate constant of compounds 129 , 130 .…”
Section: Other New Label-free Screening Strategies-unique Polymer Tec...mentioning
confidence: 99%